The Relationship between Teachers' Teaching Styles and Students' Learning Interests at SMP Negeri 1 Pancur Batu - Raditya, Brema; Dewi, Ira Kesuma (Mahesa Research Center, 2025)
This article or writing aims to determine whether there is a relationship between teacher teaching style and student learning interest. The problem is focused on the teacher's teaching style and student learning interest. The population in this study were students of SMP Negeri 1 Pancur Batu. The sample taken was 100 students taken using random sampling techniques. To approach this problem, the theoretical references from Abdul Majid regarding the types of teacher teaching styles and Totok Santoso regarding student learning interests were used. The data were collected using a questionnaire and analyzed qualitatively. In the testing process, this study used Validity and Reliability Tests, Normality Tests, Linearity Tests, and Correlation Hypothesis Tests. This study concluded that there was a relationship between teacher teaching style and student learning interest. The suggestion given in this study is that teachers should better understand what the right teaching style is for each student so that each student's learning interest can increase. With the increase in student learning interest, the quality of education will also improve because students learn with good interest.